2017
DOI: 10.1007/s10072-017-3149-5
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic potential of curcumin for multiple sclerosis

Abstract: Multiple sclerosis (MS) is a chronic autoimmune inflammatory disease of the central nervous system (CNS), characterized by demyelination, neuronal injury, and breaching of the blood-brain barrier (BBB). Epidemiological studies have shown that immunological, genetic, and environmental factors contribute to the progression and development of MS. T helper 17 (Th17) cells are crucial immunological participant in the pathophysiology of MS. The aberrant production of IL-17 and IL-22 by Th17 cells crosses BBB promote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(67 citation statements)
references
References 77 publications
0
65
0
2
Order By: Relevance
“…NF-κB is a crucial transcription factor that participates in the development of inflammatory and immune diseases activated by inflammatory responses [12,28]. In an inactive state, NF-κB binds to the I-κB member.…”
Section: Discussionmentioning
confidence: 99%
“…NF-κB is a crucial transcription factor that participates in the development of inflammatory and immune diseases activated by inflammatory responses [12,28]. In an inactive state, NF-κB binds to the I-κB member.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the ent-kauranoid diterpenoid glaucocalyxin B, isolated from the aerial parts of Rabdosia japonica, decreased NO, TNFα, IL-1β, COX-2 and iNOS in LPS-activated microglia cells [111]. These plant derivatives might represent a promising approach in targeting neuroinflammation, and different studies are aiming to define their optimal bioavailability, even if their use in clinic has yet to be defined [112,113]. Another therapeutic approach to reduce neuroinflammation is blocking necroptotic pathways with synthetic inhibitors (RIP1 inhibitors, RIP3 inhibitors, MLKL inhibitors) to mitigate NDD progression [114].…”
Section: Role Of Mitochondria and Neuroinflammation In Neurodegeneratmentioning
confidence: 99%
“…Over the past half-decade, CUR has gained attention as a key molecule in neurological disorders, being tested both for its effectiveness and safety. Numerous preclinical studies have suggested its use in treating disorders such as AD [40,41], Parkinson disease (PD) [42,43], multiple sclerosis (MS) [44,45], migraine [46,47], epilepsy [48,49], stroke [50,51], traumatic brain injury [52,53], and spinal cord injury [54]. Various studies indicate that the antioxidant, anti-inflammatory, anti-amyloidogenic, antidepressant, antidiabetic, and antiaging properties of CUR are responsible for the neuroprotective effects as in Figure 2 [55][56][57].…”
Section: Curcumin and Neurological Disordersmentioning
confidence: 99%